Previdência privada e arbitragem - Gallo, Ronaldo Guimarães (2019)
The purpose of this paper is to use arbitration to resolve conflicts arising from the Social Security System, specifically the private pension system. The characterization of the legal nature of private pension rights, especially given the constitutional framework of the architecture of these rights, the challenge emerges of the utility / possibility of private jurisdiction to resolve these conflicts. The arbitrability of the private pension issue is the challenge of this work, which, subsequently, impels the analysis of the different nuances of the legal relationship, comparing with the viability, pari passu, of the legal possibility of efficient use of arbitration. The study is based on the necessary and robust doctrinal research at home and abroad, without neglecting the historical approach to better contextualization, starting from the rule contained in the Federal Constitution, without losing sight of the nods arising from the numerous reforms that have a strong connotation in intelligence of matter. The result points to the legal feasibility of using the multiport system for the resolution of disputes arising from the private pension system, with the necessary effectiveness for the legal relations contained in this regime, especially under the approach (the perspective) of the arbitration process